Hamamelitannin Analogues that Modulate Quorum Sensing as Potentiators of Antibiotics against Staphylococcus aureus. Issue 22 (20th April 2016) - Vermote, Arno; Brackman, Gilles; Risseeuw, Martijn D. P.; Vanhoutte, Bieke; Cos, Paul; Van Hecke, Kristof; Breyne, Koen; Meyer, Evelyne; Coenye, Tom; Van Calenbergh, Serge
Abstract: The modulation of bacterial communication to potentiate the effect of existing antimicrobial drugs is a promising alternative to the development of novel antibiotics. In the present study, we synthesized 58 analogues of hamamelitannin (HAM), a quorum sensing inhibitor and antimicrobial potentiator. These efforts resulted in the identification of an analogue that increases the susceptibility of Staphylococcus aureus towards antibiotics in vitro, in Caenorhabditis elegans, and in a mouse mammary gland infection model, without showing cytotoxicity. Abstract : Don't let the bad bugs bite : Staphylococcus aureus (blue) is notorious for causing antibiotic (yellow) resistant biofilm‐related infections. The discovery of hamamelitannin as an antimicrobial potentiator led to an investigation of its structure–activity relationship. A potent and metabolically stable analogue (see structure, green) was identified that shows improved activity and drug‐like properties.